Technology-based administrative innovation and its impact on integrated islamic school management - Qiyadah Robbaniyah; Busari Afeez Babatunde (At Turots: Jurnal Pendidikan Islam, 2025)
Digital transformation in education requires schools, including integrated Islamic schools, to develop technology-based administrations to improve efficiency, transparency, and accountability. The complexity of integrated Islamic school management, which combines the general curriculum, the Islamic curriculum, as well as the full day and boarding school models, makes digital administration innovation an urgent need. This study aims to describe the implementation of technology-based administrative innovations and analyze their impact on school management, especially in the fields of personnel, student affairs, and general education. The method used is descriptive qualitative by collecting data through observation, semi-structural interviews, and documentation, then analyzed through data reduction, narrative presentation, and conclusion drawing with validity maintained through triangulation. The results of the study show that in the field of personnel, the application of digital attendance and daily to-do lists improve employee discipline and performance; in the student aspect, online PPDB, DAPODIK integration, and cashless cards facilitate data collection and involve parents; while in general education administration, the use of e-Raport, SIDIDIK, and web-based infrastructure systems increases reporting efficiency even though some processes are still manual. The research concludes that technology-based administrative innovation not only increases operational effectiveness, but also strengthens humanist work culture, transparency, and Islamic character development, so that it can become a strategic model of integrated Islamic school governance in the digital era